Aspectos epidemiologicos y moleculares de las rickettsiosis en zonas de frontera peruana - años 2011- 2012 - Palacios Salvatierra, Rosa (2014)
INTRODUCTION / RATIONALE: The rickettsial diseases are present in areas with favorable conditions such as socioeconomic and epidemiological characteristics. It is necessary to address the determinants of presentation in our country, where information is scarce. This study aims to describe some related epidemiological aspects and attempts to characterize for the first time in Peru the circulating species of rickettsiae isolated from patients and also from vectors present in four departments: Tacna, Tumbes, Loreto and Madre de Dios, which were collected during previous population-based study to detect its prevalence. OBJECTIVES: Describe some characteristic, clinical-epidemiological and genomic aspects of the circulation of rickettsias during the years 2011 and 2012 in 4 border areas of Peru. METHODS: We analyzed clinical and epidemiological data from 1,657 individuals of various age groups. The information was obtained from records stored in a previous study and past and present studies received approval by the Ethics Committee of the INS and used the same informed consent. In addition, reactivated and propagated isolates from humans and also vectors macerated, obtained during the previous study were used to perform DNA extraction and PCR tests for the htrA and gltA gene in order to proceed the genomic sequencing and identify the isolates. RESULTS: On average for the four regions, 81.35 % of individuals reported contact with potential arthropod vectors, and 56.5 % of them with domestic and peri household animals. The parameters age, sex and others were similar when comparing individuals of the 4 departments; the prevalence of regular (62%) to low (27%), housing and sanitation conditions were evidenced. 22.6 % of the cases with positive microorganism isolation were asymptomatic individuals, 45 % of them nonfebrile, thus not being good source for molecular study since they usually have a poor microbial load. As consequence, when human isolates were studied, in the first instance, only faint bands were evident in the PCR. Only after 9 to10 passages performed to spread the microbial load we could increase and continue the molecular methods for the human samples. In the order hand, we were able to perform a molecular sequencing of the vector analyzed. Sequence homology was found for Rickettsia felis isolated from Ctenocephalides canis and Rhipicephalus sanguinus; this result agrees with previous studies. In addition, we were also able to identify two species of rickettsias, i.e Rickettsia sp y Rickettsia endosymbionte, this latter not yet reported in Peru; which warrants us to continue the studies to verify these findings. CONCLUSIONS AND PERSPECTIVES: This is the first study in Peru which attempts to characterize circulating rickettsial species from human isolates from different regions of our country. It should be noted that standardization, development and implementation of specialized biological and molecular techniques, during this study is a contribution to strengthen the institutional and national capacity to achieve an effective surveillance of rickettsial diseases in Peruvian territory. Based on procedures highly effective, sensitive, specific and broad accessibility lab, which would not be possible if we do not have the necessary information about the biological, molecular and epidemiological characteristics of infectious agent involved.